Strengthening the role of Vietnam forest protection and development fund in the enforcement of the policy on payment for forest environmental services - Phan, Thị Quỳnh Hoa (2020)
In line with the international trend, the policy on payment for forest environmental services (PFES) in Vietnam has created a stable financial source for forest protection and development, increases the contribution of forestry sector in the national economy, improves livelihoods and helps to stabilize the life of forest workers. More specifically, this policy has been applied throughout the territory of Vietnam, enhancing the role and responsibility of the entire society in forest management and protection activities. To achieve that success, Vietnam forest protection and development fund (VNFF) plays a very important role in the implementation of the policy. This report will analyse in detail of VNFF with the role of an entrusted fund to mobilize, receive and utilize social resources for forest management, protection and development. Through studying legal documents in Vietnam, evaluation reports on VNFF and PFES as well as analysing data collected from surveys and interviewing stakeholders, many difficulties have been shown in the process of VNFF’s organization and operation which affects the effectiveness of the PFES policy implementation. From these findings, the author would propose some recommendations to strengthen the role of VNFF in the enforcement of the policy in the coming time